2022
DOI: 10.3390/ijerph19031154
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Depression and Anxiety in Nurses during the First Eleven Months of the COVID-19 Pandemic: A Systematic Review and Meta-Analysis

Abstract: The high risk of coronavirus (COVID-19) infection can increase the physical and psychological strain on nurses in professional practice, which can lead to mental health problems. The purpose of this systematic review and meta-analysis is to establish and estimate the combined incidence of depression and anxiety among nurses during the COVID-19 pandemic using standard measurement tools. A systematic search of the electronic databases PubMed, Web of Science, and SCOPUS was carried out to identify cross-sectional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
31
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 49 publications
1
31
2
Order By: Relevance
“…The pooled prevalence of anxiety among the HCWs during the COVID-19 pandemic was 46%. This is higher compared with the recent meta-analysis results in Africa 37%, 6 30 29% 31 in China 27% 32 in Kenya 36% 33 and global study 34.4%. 34 This is lower than study in Egypt 71.8% 35 73.3%.…”
Section: Discussioncontrasting
confidence: 63%
“…The pooled prevalence of anxiety among the HCWs during the COVID-19 pandemic was 46%. This is higher compared with the recent meta-analysis results in Africa 37%, 6 30 29% 31 in China 27% 32 in Kenya 36% 33 and global study 34.4%. 34 This is lower than study in Egypt 71.8% 35 73.3%.…”
Section: Discussioncontrasting
confidence: 63%
“…According to our results, increased COVID-19-related physical exhaustion among nurses was related to increased influenza vaccination intention. The COVID-19 pandemic increased the physical and psychological strain on nurses, leading to several mental health issues, such as depression, anxiety, post-traumatic stress disorder, stress, sleep disorders, and burnout [ 43 , 44 , 45 , 46 ]. Moreover, nurses experienced moderate-to-high levels of fear during the pandemic [ 47 , 48 , 49 , 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a metanalysis by Vizheh et al [ 14 ] showed that the mental burden affected 12% to 67% of nurses during the COVID-19 pandemic. In contrast, the meta-analysis by Ślusarska et al [ 15 ] showed that during the COVID-19 pandemic, the prevalence of depression among nurses was 22%, while anxiety disorders were experienced by 29% of them.…”
Section: Introductionmentioning
confidence: 96%